并联机构工作空间截面形状分析 - 余晓流; 刘玉旺; 储刘火 (Jixie chuandong)
The conception of equivalent rod is proposed.The section shape of workspace of the parallel manipulators,such as two-rod,three-rod and six-rod,is studied.Also the relation between mechanism parameters is analyzed to a given section shape.